Decreased Salinity Offsets the Stimulation of Elevated pCO2 on Photosynthesis and Synergistically Inhibits the Growth of Juvenile Sporophyte of Saccharina japonica (Laminariaceae, Phaeophyta) - Wenze Zhang; Yunyun Shi; Lianghua He; Xinhua Chen; Fengxiao Hu; Yinrong Chen; Yun Pang; Sufang Li; Yaoyao Chu (Plants, 2022)
The combined effect of elevated pCO2 (Partial Pressure of Carbon Dioxide) and decreased salinity, which is mainly caused by freshwater input, on the growth and physiological traits of algae has been poorly assessed. In order to investigate their individual and interactive effects on the development of commercially farmed algae, the juvenile sporophytes of Saccharina japonica were cultivated under different levels of salinity (30, 25 and 20 psu) and pCO2 (400 and 1000 µatm). Individually, decreased salinity significantly reduced the growth rate and pigments of S. japonica, indicating that the alga was low-salinity stressed. The maximum quantum yield, Fv/Fm, declined at low salinities independent of pCO2, suggesting that the hyposalinity showed the main effect. Unexpectedly, the higher pCO2 enhanced the maximum relative electron transport rate (rETRmax) but decreased the growth rate, pigments and soluble carbohydrates contents. This implies a decoupling between the photosynthesis and growth of this alga, which may be linked to an energetic reallocation among the different metabolic processes. Interactively and previously untested, the decreased salinity offset the improvement of rETRmax and aggravated the declines of growth rate and pigment content caused by the elevated pCO2. These behaviors could be associated with the additionally decreased pH that was induced by the low salinity. Our data, therefore, unveils that the decreased salinity may increase the risks of future CO2-induced ocean acidification on the production of S. japonica.